EFFECTS OF COMBINED ETHANOLIC EXTRACTS OF CITRULLUS COLOCYNTHIS AND PLUMBAGO ZEYLANICA (L) ON MCF-7 HUMAN BREAST CANCER CELL LINES - G. Geetha (The Bioscan, 2025)
Background: Breast cancer is the most common disease in both developed and developing countries. According to the World Health Organization, breast cancer is the most prevalent cancer amongwomen worldwide and the second most common cause of cancer death in women. Annually, breast cancer causes over 1 million new cases, results in more than 400,000 deaths, and about 4.4 million women live with breast cancer. Aim: The study aims to investigate the combined effect of the ethanolic extracts of Citrullus colocynthis and Plumbago zeylanica Linn on the MCF-7 human breast cancer cell line. Methodology: The phytochemical screening was performed on the combined ethanolic extractof Citrullus colocynthis and Plumbago zeylanica Linn to identify the presence of alkaloids, terpenoids, flavonoids, tannins, and coumarins. GC-MS analysis was performed using thermoGC Trace Ultra Version 5.0 to determine the possible chemical compounds in the extract. Moleculardocking was performedforthetargetproteinestrogenreceptoralpha(ER-α),retrieved from the RCSB PDB (ID: 3ERT). MTT assay performed to determine the anti-proliferative activity of the combined ethanolic extract with different concentrations such as 6.25, 12.5, 25,50, and 100 µg/ml on MCF-7 human cancer cell line. The caspase3 and 9 inhibition assays were performed to demonstrate the cell death and apoptosis induced by the combined extract. Result: GC-MS analysis revealed 16 chemical components present in the extracts. In that, 9- octadecenamide 50.43%, 1,2-benzenedicarboxylic acid, dioctyl ester 11.25% were predicted to be present in larger quantities. Molecular docking studies proved that the polyphenoliccompoundhasgoodbindingaffinitywithER-α,withaglidescorerangeof- 9.85kcal/molto-5.98 kcal/mol, compared to tamoxifen, which has a glide score of -10.28 kcal/mol. Cytotoxicity measured as IC50 against the MCF-7 cell line was found to be 34.57 µg/ml. The extract was able toincreasetheactivityofcaspase3 and9, indicatingtheextract was ableto induceapoptosisand cell death. Conclusion: According to the results, we concluded that the combined ethanolic extract of Citrullus colocynthis and Plumbago zeylanica linn act as potential chemotherapeutic agent for breast cancer. KEYWORDS: High-risk pregnancy, warning signs, awareness program, antenatal mothers, maternal health.